2013
DOI: 10.1038/jp.2013.96
|View full text |Cite
|
Sign up to set email alerts
|

Superiority of targeted neonatal echocardiography for umbilical venous catheter tip localization: accuracy of a clinician performance model

Abstract: TnECHO is superior to chest radiography for identifying malpositioned catheters. TnECHO performed by pediatric housestaff physicians with basic training, demonstrated high-accuracy rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 11 publications
1
44
0
1
Order By: Relevance
“…Peripherally inserted central catheters are critical tools for neonatal providers, and safe, efficient bedside imaging tools may help decrease PICC complication rates. The use of US to localize central lines in the NICU has been well described . Ultrasound‐guided PICC placement has been shown to decrease line manipulations and radiographs, but US for ongoing PICC monitoring has not been widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Peripherally inserted central catheters are critical tools for neonatal providers, and safe, efficient bedside imaging tools may help decrease PICC complication rates. The use of US to localize central lines in the NICU has been well described . Ultrasound‐guided PICC placement has been shown to decrease line manipulations and radiographs, but US for ongoing PICC monitoring has not been widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the recent consensus is that echocardiography should be considered to confirm correct placement of UVCs. A recent study reported that echocardiography carried out by trained house-staff paediatricians to determine the UVC tip position had a high accuracy rate with an area under the receiver operating characteristic curve of 0.81, when compared with scans performed by a cardiologist 13. Hence training treating physicians and house-staff paediatricians in—and making them aware of the need for—echocardiography to confirm UVC placement is not only more feasible but is also reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Bedside sonography is becoming the gold standard to confirm UVC position 13. Radiography has been found to be unreliable, because the level of the IVC right atrial junction was seen to vary widely from T6-T11 6.…”
Section: Discussionmentioning
confidence: 99%
“…Hoellering et al 14 found that the cardiac silhouette method was superior to the vertebral level method to confirm the UVC position in the abdominal radiograph, but the diagnostic accuracy of both the methods was found to be less when compared to sonography. Studies have shown that sonography identified malposition of the catheter in cases in which the position of the catheter on the X-ray was found to be normal 6 13. However, the unavailability of a good ultrasound machine with appropriate probes and lack of expertise limit the use of sonography to confirm UVC position in many centres.…”
Section: Discussionmentioning
confidence: 99%